2018
DOI: 10.1021/acs.langmuir.8b03555
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Forces between Supported Cationic Bilayers by Colloid Probe Atomic Force Microscopy: Electrolyte Concentration and Composition

Abstract: The interactions between supported cationic surfactant bilayers were measured by colloidal probe atomic force spectroscopy and the eect of dierent halide salts was investigated. Di(alkyl iso-propyl ester) dimethyl ammonium methylsulfate (DIPED-MAMS) bilayers were fabricated by the vesicle fusion technique on muscovite mica.The interactions between the bilayers were measured in increasing concentrations of 1 NaCl, NaBr, NaI and CaCl 2 . In NaCl the bilayer interactions were repulsive at all concentrations inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This suggestion might be in contrast to a general assumption that SLBs do not fluctuate due to their strong interaction with the substrates. 19,25 Our measurements on DOAB, DTDAB, and DODAB systems might cast doubt on whether such an assumption always holds true or not. X-ray or neutron scattering methods have been also applied to measure dynamic properties of soft materials supported on solid substrates and they yield fruitful information.…”
Section: Resultsmentioning
confidence: 91%
“…This suggestion might be in contrast to a general assumption that SLBs do not fluctuate due to their strong interaction with the substrates. 19,25 Our measurements on DOAB, DTDAB, and DODAB systems might cast doubt on whether such an assumption always holds true or not. X-ray or neutron scattering methods have been also applied to measure dynamic properties of soft materials supported on solid substrates and they yield fruitful information.…”
Section: Resultsmentioning
confidence: 91%
“…Such a celebrated theory is based on the assumption that interactions can be expressed as a superposition of two main components: an attractive and short-range van der Waals potential and a repulsive long-range one, described as an electric double layer (EDL). In charged vesicle suspensions of industrial interest, however, the EDL repulsion is often found to be the only relevant component, while the van der Waals contribution is definitely negligible [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The values of the interaction strength and range used in our simulations are taken from recent experiments that directly measured the force between bilayers of cationic quaternary ammonium surfactants in solutions, over a wide range of halide salts concentrations. In particular, we focus on the measurement in the presence of NaI salt at four different concentrations [14]; lowering the salt concentration corresponds, in our simulations, to increasing strength and range of the EDL repulsion. The volume fraction is varied between 0.02 and 0.55, enclosing the range of dilution typically used in real production [8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, surface force measurements by AFM allow us to investigate various surfaces. (10)(11)(12) We often employ colloidal probes in AFM measurements, for which a silica or polystyrene colloid with a diameter of several to several tens of µm [Fig. 1(a)] is fixed at the end of the cantilever.…”
Section: Interactions In Water: Dlvo and Non-dlvo Forcesmentioning
confidence: 99%